Classes of I-Convergent Double Sequences over n-Normed Spaces. (9th May 2016) - Khan, Nazneen
Abstract : I introduce some new classes of I -convergent double sequences defined by a sequence of moduli over n -normed space. Study of their algebraic and topological properties and some inclusion relations has also been done.